If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 + 16x = 15x Solving 26 + 16x = 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 26 + 16x + -15x = 15x + -15x Combine like terms: 16x + -15x = 1x 26 + 1x = 15x + -15x Combine like terms: 15x + -15x = 0 26 + 1x = 0 Add '-26' to each side of the equation. 26 + -26 + 1x = 0 + -26 Combine like terms: 26 + -26 = 0 0 + 1x = 0 + -26 1x = 0 + -26 Combine like terms: 0 + -26 = -26 1x = -26 Divide each side by '1'. x = -26 Simplifying x = -26
| 54=16v | | X+2=-10+4x | | 6(0.5+1)= | | (8x/5)/(1-3/10) | | 9546x-3440=86(111x-40) | | 6x+7=-5+7x | | 8c-2d= | | 7x+2=2-2x | | 4(10x+1)=40x-5 | | 13x+2(2x+1)=10 | | h/8-13=12 | | 0.002+15=2n | | 29-7c=-4(9c+5) | | 3(5n-4)=n+2 | | X-8-5x=-44 | | 37-6x=13-9 | | 7x+3=7x-8 | | (4b-9)12=-64 | | X-8-5x=-4 | | x*5-1=x^3+3 | | 19/20-5/6 | | e^5k=1-0.67 | | 2x+3=4h+5 | | 17=3x-7x+9 | | 8x-4+6x+4+x= | | d/0.2=3d=2.1 | | 54=6v | | e^5*k=1-0.67 | | 6-9x=10+x | | x-4/9=-1 | | 4y^2-5y+49=0 | | -8+5x+3x=-32 |